Enhancing Regional Growth through Thematic Tourism Packages: A Case Study from Tapanuli Tengah Regency, Indonesia.: English - Maulana, Utama Graha; Agus Purwoko; Lindawati (Asian Multidisciplinary Research Journal of Economy and Learning, 2025)
This research investigates the potential for regional development through thematic tourism packages in Tapanuli Tengah Regency, Indonesia. Employing a mixed-methods approach that combines qualitative descriptive analysis with quantitative tools such as SWOT and the Tourism Object and Attraction Evaluation Guidelines (ODTWA), the study assesses four tourist destinations: Makam Papan Tinggi, Kalimantung Island, Sipitu-pitu Waterfall, and Aek Bottar Waterfall. The findings reveal that Makam Papan Tinggi and Kalimantung Island are highly suitable for development, while the other two require infrastructure upgrades, particularly in terms of access and lodging facilities. The Strengths-Opportunities (SO) strategy emerges as the most effective option for fostering sustainable tourism, highlighting the importance of local community engagement and supportive public policies. The study concludes that a well-coordinated tourism package can boost regional revenue and improve community well-being, offering a scalable model for other regions with rich but underdeveloped tourism assets.